(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2007)
The article describes how the behaviour of sunlight on the stonework at two points in the nave of Arbroath Abbey allows the moment of astronomic noon (Greenwich mean time plus ten minutes) to be identified between the months of September and March.